Instability after Total Knee Arthroplasty - McNabb, David Clinton; Kim, Raymond H.; Springer, Bryan D. (The Journal of Knee Surgery, 2015)
Total knee arthroplasty (TKA) has shown to portend good long-term survivorship and excellent patient satisfaction. There are various etiologies of failure of a TKA. Instability is a major cause of the need for revision. Often, increased constraint is needed to supplement or perform the function of incompetent ligament and soft tissue structures. Posterior cruciate retaining (PCR) TKA has the least constraint. Posterior cruciate substituting (PS) TKA increases sagittal constraint. Varus–valgus constraint (VVC) adds a marked increase in coronal stability. The ultimate in constraint in TKA is a linked hinged implant. In revision TKA, it is the surgeon's responsibility to implant the prosthesis with the necessary constraint to impart adequate stability.
Keywords: knee; arthroplasty; instability; revision